FRI0505 Efficacy and Tolerability of Rituximab in Idiopathic Inflammatory Myopathies in A Monocentric Experience. (10th June 2014) - Barsotti, S.; Neri, R.; Talarico, R.; Iacopetti, V.; Tavoni, A.; d'Ascanio, A.; Bombardieri, S.
Abstract : Background: High doses of corticosteroids (CS) alone or in association with (and/or) traditional immunosuppressive drugs are considered the first choice treatment of idiopathic inflammatory myopathies (IIM). Patients refractory to traditional therapy may be candidate to other therapeutic agents, including rituximab (RTX). Objectives: The primary objective of the study was to assess the efficacy of RTX on disease activity in patients with refractory PM/DM; the secondary aim was represented by the evaluation of adverse events (AE) during the treatment period. Methods: All patients referred to our rheumatology unit and treated with RTX were enrolled. Treatment schedule was represented by RTX 1000 mg i.v. twice, with a 2-week interval. Retreatment with RTX was conducted just in case of disease relapse and at least after 6 months. Cumulative end-points were: indication to start treatment, previous and concomitant therapies, cumulative CS dose, serum creatinkinase (CK) levels, disease activity by means of a physician visual analogic scale (pVAS), number and timing of retreatment, patients' reported improvement (score 0-2). Results: From Jan 2003 to Nov 2013, eighteen patients, pts, (M/F:7/11; mean age 50.3±16 years; mean disease duration 65±66 months) with biopsy proven IMM (10 polymyositis, 4 dermatomyositis, DM, 1 inclusion body myositis, 3 myositis associated with connective tissue diseases) were treated with RTX. Indications to start treatment were: active muscular involvement in all pts (CK levels, muscular strength and/or presence of muscle edema at MRI), dysphagia (6 pts), DM skin rash (3) and arthritis (2). Previous treatments were: in all patients i.v. 6-methilprednisolone pulses (500 mg) or high doses (1 mg/kg/die). The mean cumulative CS dose was 9.5 gr. The CS therapy was combined in all patients with almost one DMARDs: 10 methotrexate (MTX), 9 cyclosporine (CYA), 5 cyclophosphamide, 3 azathioprine, 3 mycophenolate mophetile (MMF); 15 patients were treated with intravenous immunoglobulins (IvIg). At six months, the mean CK levels were significantly reduced by 87%, compared with baseline. Mean levels of pVAS were reduced by 7.5 cm to 3.7 cm. Moreover, muscle strength improved in 13 pts and only two pts were bedridden. Dysphagia improved in 4/6 pts, dyspnea in 2/2, artrhtitis in 2/2. DM skin manifestation did not improve. The mean follow up time was 38 months (min-max 7-142). 17/18 pts continued treatment with low dose CS, 11 combined with a DMARD (6 CYA, 3 MTX, 2 MMF). Six pts are continuing therapy with IvIg. At 1 year after the first infusion only 2 pts needed a retreatment for a IIM flare, that was efficacy. Regarding AE, 1 pt developed a severe CMV lung infection, 1 a mild bladder infection, 1 developed a severe erythematous rash few days after the first infusion and 2 presented an anaphylactic reaction during the second infusion. One 52 year-old male patient without history of cardiac disease died 1 month after the third treatment for sudden cardiac death. Conclusions: According to literature data, our results have confirmed the effectiveness of RTX in the treatment of IIM. Although the safety profile does not seem free from adverse events and further ad hoc controlled trials are needed to better clarify a specific schedule of management. RTX surely represents a new perspective for the therapeutic approach of IIM Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2502